(untitled) (Global Journal of Human-Social Science, 2023)
This paper reports the results of a piece of research conducted in two rural communities in Ghana to explore their perceptions on the concept of literacy The research was framed by the theory of literacy as Social Practice which conceives literacy as multiple and embedded in the daily lives of people rather than as a single uniform skill that can be acquired in a neutral and independent environment and then applied to every situation I used the qualitative methodology and the case study method to enable me to collect data in a natural setting and understand the focus of the research from the perspectives of the research participants Twenty-two research participants from the two communities were purposely selected to achieve a fair representation of the communities The findings of the research revealed that for the people of Juas o and Saaman where the research was conducted literacy is not limited to the ability to read and write even though this is seen to be important